Making Constitutions, From the Perspective of a Constitutional Adviser - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 2002)
This article summarises the author’s experience of creating constitutions for the State of Niue, the Republic of the Marshall Islands, and the Republic of Fiji. She sets out eight general issues of discussion. First, when do countries make a new constitution? Secondly, how do constitutions act as the rules of the political game? Thirdly, how can a country make a constitution? Fourthly, how does the method of constitution-making affect the tasks of the constitutional adviser? Fifthly, should the public be involved in constitution-making, and how? Sixthly, what goes into a constitution? Seventhly, is the Westminster constitution a satisfactory export model? Finally, what are the responsibilities of a constitutional adviser? The author discusses all issues by providing her experiences in the above nations, setting the scene for a discussion of constitution-making in New Zealand.